Pola pencarian informasi mahasiswa Program Studi Perpustakaan dan Sains Informasi UKSW menggunakan teori Ellis - David Septian; Albertus Pramukti Narendra; Anton Hermawan (Jurnal Kajian Informasi dan Perpustakaan, 2021)
Satya Wacana Christian University (SWCU) Library and Information Science Study Program students have studied information science at an early study stage, so they consistently seek information. This study aimed to investigate the information-seeking patterns of the SWCU Library and Information Science Study Program students using Ellis' theory. This study used descriptive quantitative research methods. Determination of respondents used quota sampling for active students from class 2015 to 2019 using Google forms. Based on the study results, respondents searched for information according to information-seeking behavior: starting, chaining, browsing, differentiating, monitoring, and extracting activities. Respondents in starting activities can already determine the topic of information before seeking the information needed, with a value of 82.6%. Respondents in chaining activities could relate the information obtained through the initial search, with a value of 83.4%. Respondents in browsing activities could search for information in a structured manner, with a value of 78.4%. Respondents in differentiating activities could categorize the information needed, with a value of 83%. Respondents in monitoring activities always made notes after obtaining the required information development, with a value of 79.1%. Respondents in extracting activities could ensure the accuracy of the information obtained through scanning techniques, with a value of 77.9%. However, there was a shift in the Ellis model of information-seeking patterns because some respondents had several stages of information-seeking. The conclusion is that the development of information technology has influenced the student's information-seeking pattern.